Surgical Site Infection Following Caesarean Section by Acinetobacter Species: A Report from a Hyperendemic Setting in the Brazilian Amazon Region - Blenda Gonçalves Cabral; Danielle Murici Brasiliense; Ismari Perini Furlaneto; Yan Corrêa Rodrigues; Karla Valéria Batista Lima (Microorganisms, 2021)
Surgical site infection (SSI) following caesarean section is associated with increased morbidity, mortality, and significant health care costs. This study evaluated the epidemiological, clinical, and microbiological features of Acinetobacter spp. in women with SSIs who have undergone caesarean section at a referral hospital in the Brazilian Amazon region. This study included 69 women with post-caesarean SSI by Acinetobacter spp. admitted to the hospital between January 2012 and May 2015. The 69 Acinetobacter isolates were subjected to molecular species identification, antimicrobial susceptibility testing, detection of carbapenemase-encoding genes, and genotyping. The main complications of post-caesarean SSI by Acinetobacter were inadequate and prolonged antibiotic therapy, sepsis, prolonged hospitalization, and re-suture procedures. A. baumannii, A. nosocomialis and A. colistiniresistens species were identified among the isolates. Carbapenem resistance was associated with OXA-23-producing A. baumannii isolates and IMP-1-producing A. nosocomialis isolate. Patients with multidrug-resistant A. baumannii infection showed worse clinical courses. Dissemination of persistent epidemic clones was observed, and the main clonal complexes (CC) for A. baumannii were CC231 and CC236 (Oxford scheme) and CC1 and CC15 (Pasteur scheme). This is the first report of a long-term Acinetobacter spp. outbreak in women who underwent caesarean section at a Brazilian hospital. This study demonstrates the impact of multidrug resistance on the clinical course of post-caesarean infections.